German Diabetes Study – Baseline data of retinal layer thickness measured by SD‐OCT in early diabetes mellitus. Issue 2 (21st September 2018) - Schröder, Katharina; Szendroedi, Julia; Benthin, Anna; Gontscharuk, Veronika; Ackermann, Philipp; Völker, Magdalena; Steingrube, Nadine; Nowotny, Bettina; Ziegler, Dan; Müssig, Karsten; Geerling, Gerd; Kuß, Oliver; et al.
Abstract: Purpose: Recent studies highlighted that early diabetic neurodegeneration is present before microvascular changes are visible. Retinal neurodegeneration can decrease retinal layer thickness. We aimed to determine whether decreased retinal layer thickness is present already in the early time course of disease. Methods: A cross‐sectional analysis of patients and healthy adults from the German Diabetes Study (GDS, ClinicalTrials.gov Identifier number: CT01055093, https://clinicaltrials.gov/ct2/show/NCT01055093 ). Inclusion criteria were a diagnosis of diabetes mellitus (DM) within the last 12 months. Retinal layers thickness in the nasal pericentral segment was measured by spectral domain ocular coherence tomography (SD‐OCT). For statistical analysis proc mixed (sas ‐version 9.4) was used. Results: One hundred and seventy‐eight eyes of 89 patients with type 1 DM (58 males, age 36 ± 11 years, BMI 25.5 ± 4.2 kg/m²) and 242 eyes of 121 patients with type 2 DM (84 males, age 53 ± 10 years, BMI 31.9 ± 6.3 kg/m²) with a disease duration of less than 1 year were compared to 76 eyes of 38 controls (27 males, age 41 ± 16 years, BMI 27.3 ± 6.4 kg/m²). Analysis of retinal layer thickness and visual function did not reveal a significant difference between patients and controls. Conclusion: In the early course of DM potential, neurodegeneration does not relate to measureable changes of retinal layer thickness.